Antibacterial Activity Test, Evaluation of Pharmacognosy and Phytochemical Screening of Some Extracts of Globe Amaranth (Gomphrena globosa) - Kusmiati Kusmiati; Dody Priadi; Romah K.B. Rahayu (Chemistry Department, The University of Brawijaya, 2017)
Indonesia is a rich biodiversity country where various medicinal plants are existed. One species of medicinal plants is Globe Amaranth (Gomphrena globosa, Amaranthaceae). This species is native to Central America and has been widely spread to the tropics. To date the species can be easily found at the home gardens as an ornamental plant. Medicinal plants has been used for generations by traditional people. It was empirically proven that medicinal plants have ability to cure certain diseases such as dysentery. All parts of this plant can be used as medicine. However, only the flower of the species was used in this study. Objective of the study was to identify the highest antimicrobial activity of Gomphrene globosa flower extract using ethanol, petroleum ether, ethyl acetate and n-butanol solvents. Gomphrena globosa flower was extracted using 96% ethanol and then was by partitied using petroleum ether, ethyl acetate and n-buthanol respectively. The extracts were then evaporated using a rotapavor until condensed extract was obtained. Phytochemical screening was done on both of the flower powder and extract. Result of Pharmacognosy evaluation of the Globe Amaranth flower as follows: water content 8.17%, total ash content 9.11%, acid-insoluble ash 1.50%, acid-soluble ash 6.43%, water-soluble extract 10.79%, ethanol-soluble extract 3.51% and dry content 10.19%. The condensed extracts were tested for antimicrobial activity against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Shigella dysenteriae. Result of antibacterial activity test by agar diffusion method showed that the higner concentration of the extract led to higher bacterial inhibition zone. The highest antimicrobial activity was obtained from n-butanol extract as indicated by a significant inhibition zone around paper disk